If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6 + -7x) = -105 (6 * 7 + -7x * 7) = -105 (42 + -49x) = -105 Solving 42 + -49x = -105 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -49x = -105 + -42 Combine like terms: 42 + -42 = 0 0 + -49x = -105 + -42 -49x = -105 + -42 Combine like terms: -105 + -42 = -147 -49x = -147 Divide each side by '-49'. x = 3 Simplifying x = 3
| 4x^2+5=x | | 4x^2-3x-9-(2x^2+22x+27)=0 | | 8(4x+8)-1=287 | | 2x^2-25x-36=0 | | 7(5-3n)=-112 | | x*3+10=11+x | | 7(1-5n)=182 | | 4=2e^14x-1 | | 85=n-6(-n-6) | | 6(x-2)+6=4(2x-6) | | 6x-1=11x-11 | | 6(1+3p)=-138 | | 2x-42=-6(x+3) | | (15+11x)=(18+8x) | | 2+5(8n+3)=217 | | 15+11x=y | | -105=-8(n+7)-1 | | 9x-7-4x=-14 | | 5(84+-0.6y)+3y=420 | | -92=-8(4n-4)+4 | | -w+245=288 | | x^2+2y-8=0 | | -3p+4=22 | | 0=-16t^2+47t+0 | | 158=-u+208 | | 5+3x=30 | | 0=16t^2+47t+0 | | 6x^2=2x+14 | | 246-w=183 | | -4+3(1+4p)=95 | | 3.36-x=0.08 | | -11x+-4= |